Influence cheerleading exercise on evaluation degree coordination abilities of schoolchildren of the 5–6th forms of the comprehensive school - Бала, Т. (Slobozhanskyi Herald of Science and Sport, 2011)
Development level indices of the coordination abilities and their evaluation degree under the influence of cheerleading exercises among the schoolchildren of the 5–6th forms of the comprehensive school are presented in this article. Cheerleading exercise usage positively influence on demonstrated coordinating abilities degree of secondary school children by all investigated parameters.